Assessment of facial analysis measurements by golden proportion, - Kaya,Kerem Sami (2019)
Abstract Introduction: The face is the most important factor affecting the physical appearance of a person. In facial aesthetics, there is a specific mathematical proportion, which is called golden proportion, used to measure and analyse facial aesthetic qualities in population. Objectives: The aim of this study was to measure the facial soft tissue proportions which would help to constitute a standard for facial beauty and diagnose facial differences and anomalies and to compare these proportions to the golden proportion. Methods: One hundred and thirty-three (133) Turkish patients 18-40 years of age (61 females, 72 males) were involved in the study. Analysis of the photographs was performed by the same physician, and a software programme was used (NIH Image, version 1.62). Facial proportions were measured and differences from the golden proportions were recorded and grouped as normal (1.6-1.699), short (<1.6) and long (>1.699). Results: According to the facial analysis results, the trichion-gnathion/right zygoma-left zygoma was assessed: 33.1% of the patients were in normal facial morphology, 36.8% were in long facial morphology and 30.1% were in short facial morphology, according to this proportion. The trichion-gnathion/right zygoma-left zygoma proportion was significantly higher in males than females (p < 0.001). Statistically significant difference was noted in gender groups, according to the trichion-gnathion/right zygoma-left zygoma and the right lateral canthus-left lateral canthus/right cheilion-left cheilion proportions (p = 0.001, p = 0.028). Conclusion: Facial proportion assessments in relation to the golden proportion showed that a statistically significant difference was observed between gender groups. Long facial morphology was observed more in males (51.4%); normal (41%) and short (39.3%) facial morphology were more common in females. The measurements and proportions for facial balance in our study population showed that the facial width and height proportions deviated from the golden proportion.